Trabalhadoras e trabalhadores de Caruaru (PE) no contexto de desenvolvimento da feira da sulanca : labutas e (res)significação (1980 - 2015) - Nascimento, Julio Cesar dos Santos (2023)
In the city of Caruaru, in the interior of Pernambuco, there is one of the largest fairs in Brazil, called Sulanca. This commercial space has a formation that intrigues us, as this fair is part of a large production chain triggered by some processes that occurred throughout the second half of the 20th century, such as the implementation of a new economic activity, sewing and production of clothing as a complement to agricultural income, and, later, as a substitute for agricultural activities. Located in the already consolidated area of social history of work, this Dissertation aims to demonstrate how Sulanca was formed, in the municipality of Caruaru, in Agreste Pernambucano, in the years 1980 to 2015, and how this fair is linked to another commercial enterprise that Here we will call it a “traditional fair”, which takes place weekly and has existed since the mid- to late 18th century, in the search to understand how Sulanca connects other fairs and cities over time. We will also seek to demonstrate how stallholders produce their goods and what labor conditions they were subjected to, in order to broaden our perspective on Sulanca, especially placing it in a process of labor and exploitation.